Peran Mahasiswa IAKN Tarutung dalam Pelayanan Melalaui KPPM di Gereja Bnkp Fa`Omasi Tarutung - Meliana Hutabarat; Rahel Lumbantobing; Misilina Zalukhu; Jemie Riando Manik (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The Community Service and Practical Fieldwork Program (KPPM) serves as a tangible form of social responsibility by encouraging students to engage in meaningful activities that positively impact society. In the 2025/2026 academic year, IAKN Tarutung conducted this program involving undergraduate students, including those enrolled in the Christian Religious Education (PAK) and Church Music Education (PMG) departments. One of the designated locations for this program was Hutauruk Village in Tarutung District, North Tapanuli Regency. This study centers on the implementation of the KPPM program in Hutauruk Village, which ran from March to June 2025 and engaged students from IAKN Tarutung. The primary objectives of this research are to explore the spiritual challenges faced by the community, to present solutions developed during the program, to assess the overall impact of KPPM on the local residents, and to examine how participation in the program contributes to the students’ personal and professional development. A qualitative research approach was employed, using methods such as participatory observation, interviews, and literature review. The findings indicate that students are required to assist the BNKP (Banua Niha Keriso Protestan) Fa’omasi Tarutung Church community by working collaboratively, demonstrating creativity, actively participating, and applying effective problem-solving strategies.